Exploitation of thin mantles, applying the method Chambers and Pillars with Central Gallery and Stepped Pillars - Mina Aztlan 2 - Jalisco - Mexico - Arce Gonzáles, Luís Alberto (2020)
In underground mining, the exploitation of mantles of thicknesses less than 1.20 m, becomes difficult and very often its cost of mining is high, this due to the traditional exploitation method that is usually used. This work aims to propose a new exploitation design and provide a solution to the operational problem in the Aztlan 2 Mining Unit in Autlán de Navarro - Jalisco Mexico, where the mantle with manganese mineral content is less than 1.20 m thick. For which a variant of the camera and pillars method was designed, which has been called: cameras and pillars with central gallery and stepped pillars or simply T Room, allowing to reduce the cost of mining of US $ 59.00 dollars the ton extracted at US $ 38.00 dollars, also gives greater speed to the exploitation and pass production of 200 Tons / month in a traditional way to 3400 tons / month, using this new variant. The application of this variant shows that it is economically viable for structures that have similar characteristics, that is to say they have competent boxes and whose thicknesses are less than 1.2 m.